2022
DOI: 10.5267/j.uscm.2022.8.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply chain 4.0 technologies on its strategic outcomes

Abstract: The aim of this study is to explore the impact of supply chain 4.0 technologies (e.g., big data and Internet-of-things) of the strategic outcomes of supply chain 4.0. The required data was collected via a questionnaire from a sample consisting of 211 employees from construction companies in Jordan. The results point out that big data and the Internet of things have significant impacts on the strategic outcomes of supply chain 4.0. Hence, it was concluded that supply chain technologies are pivotal drivers of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Delivery is also positively impacted with, for example, product delivery being more accurate [41]. Cost performance is also enhanced due to the use of analytics in SC 4.0 [43], for example, inventory costs due to a better forecast process [44] or operation and communication costs [8]. Handanga et al (2021) [42] reported that big data analytics can reduce costs by 20-50%.…”
Section: Analysis Of the Papersmentioning
confidence: 99%
See 4 more Smart Citations
“…Delivery is also positively impacted with, for example, product delivery being more accurate [41]. Cost performance is also enhanced due to the use of analytics in SC 4.0 [43], for example, inventory costs due to a better forecast process [44] or operation and communication costs [8]. Handanga et al (2021) [42] reported that big data analytics can reduce costs by 20-50%.…”
Section: Analysis Of the Papersmentioning
confidence: 99%
“…A further positive aspect concerns quality [46]. One of the strategic benefits is improvements in quality for both products and services [8].…”
Section: Analysis Of the Papersmentioning
confidence: 99%
See 3 more Smart Citations